An asymmetric oxygen vacancy iron cerium composite oxide adsorbent and a preparation method and application thereof

CN122875189APending Publication Date: 2026-10-09JIANGXI UNIV OF SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611124972.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,常规铁基吸附剂存在显著缺陷:(1)抗烧结性能差,在高温(>800℃)烟气条件下易发生烧结团聚,导致比表面积急剧下降,活性位点减少;(2)吸附温度窗口窄,通常在特定温度区间(如200℃~400℃)内性能较好,难以适应复杂多变的工业烟气工况;(3)吸附效果不佳,对As2O3的氧化和固定能力有限,吸附容量不高

Benefits of technology

1.本发明通过铈掺杂构建的Fe2+-[O]-Ce3+非对称氧空位,极大地增强了吸附剂的氧化能力。该氧空位既能活化烟气中的游离氧分子(O2),又能促进自身晶格氧的迁移,两者协同高效地将剧毒的As2O3氧化为易于固定的As2O5,较未改性的H-Fe2O3提升了砷吸附能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875189A_ABST
    Figure CN122875189A_ABST
Patent Text Reader

Abstract

The application provides an asymmetric oxygen vacancy iron cerium composite oxide adsorbent and a preparation method and application thereof, and belongs to the technical field of waste gas adsorbents. The adsorbent is a microsphere with a hollow mesoporous structure, and a shell layer of the microsphere is formed by stacking of iron cerium oxide composite amorphous nanosheets with an average particle size of 5nm-10nm. The preparation method comprises the following steps: adding urea, sodium citrate, ferric nitrate and cerium nitrate into deionized water, stirring uniformly, adding isopropyl alcohol, uniformly mixing to form a precursor solution, microwave heating the precursor solution to a target temperature, keeping the temperature, naturally cooling to room temperature, centrifugal separation to collect the precipitate, washing and drying to obtain black precipitate, placing the black precipitate in a muffle furnace, calcining under a nitrogen atmosphere, naturally cooling, washing, filtering and drying to obtain a deep red powder. The Fe 2+ -[O]-Ce 3+ Asymmetry oxygen vacancy greatly enhances the oxidation capacity of the adsorbent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of waste gas adsorbent technology, and specifically relates to an asymmetric oxygen-vacancy iron-cerium composite oxide adsorbent, its preparation method, and its application. Background Technology

[0002] Arsenic and its compounds are highly toxic pollutants with carcinogenic, teratogenic, and mutagenic effects. Gaseous arsenic trioxide (As2O3) in industrial flue gas (especially non-ferrous smelting and coal-fired flue gas) is its main form of existence, posing a serious threat to the environment and human health.

[0003] Currently, iron-based adsorbents (such as Fe2O3) are widely studied for arsenic removal due to their abundant raw materials and low cost. However, conventional iron-based adsorbents have significant drawbacks: (1) poor anti-sintering performance, easily sintering and agglomerating under high-temperature (>800℃) flue gas conditions, resulting in a sharp decrease in specific surface area and a reduction in active sites; (2) narrow adsorption temperature window, usually performing well within a specific temperature range (such as 200℃~400℃), making it difficult to adapt to complex and variable industrial flue gas conditions; (3) poor adsorption effect, limited ability to oxidize and fix As2O3, and low adsorption capacity.

[0004] Although previous studies have prepared H-Fe2O3 adsorbents by constructing hollow structures, which has improved the anti-sintering properties and broadened the temperature window to some extent, there is still room for improvement in its oxidation capacity, especially in the key step of oxidizing As2O3 for gaseous arsenic capture.

[0005] Therefore, developing a novel arsenic removal adsorbent that combines high adsorption capacity, wide temperature range activity, excellent anti-sintering and anti-acid corrosion capabilities is a technical problem that urgently needs to be solved in the field of flue gas purification. Summary of the Invention

[0006] In view of this, the present invention provides an asymmetric oxygen-vacancy iron-cerium composite oxide adsorbent, its preparation method and application, aiming to solve at least one technical problem in the background art.

[0007] This invention is implemented as follows: The first aspect of this invention provides an asymmetric oxygen-vacancy iron-cerium composite oxide adsorbent, wherein the adsorbent is a microsphere with a hollow mesoporous structure, the microsphere having a diameter of 1 μm to 2 μm and a shell thickness of 50 nm to 100 nm, the shell being formed by stacking iron-cerium oxide composite amorphous nanosheets with an average particle size of 5 nm to 10 nm, and Fe is constructed through cerium doping. 2+ -[O]-Ce 3+ Asymmetric oxygen vacancies.

[0008] Another aspect of the present invention provides a method for preparing an asymmetric oxygen-vacancy iron-cerium composite oxide adsorbent, the preparation method comprising the following steps: S1. Preparation of precursor solution: Add urea, sodium citrate, ferric nitrate and cerium nitrate in a preset ratio to deionized water, stir evenly, then add isopropanol and mix evenly to form a precursor solution. S2. Three-dimensional structure construction: The precursor solution is microwave heated to the target temperature and kept at that temperature, then naturally cooled to room temperature. The precipitate is collected by centrifugation, washed with ethanol, and then vacuum dried until the water is completely evaporated to obtain a black precipitate. S3. Calcination to remove template: The black precipitate is placed in a muffle furnace and calcined in an oxygen atmosphere. After natural cooling, it is washed and filtered with anhydrous ethanol and deionized water, and dried to obtain a dark red powder.

[0009] Further, in S1, 0.7 mmol to 0.9 mmol of urea, 0.04 mmol to 0.06 mmol of sodium citrate, 0.4 mmol to 0.6 mmol of nitric acid, and 0.05 mmol to 0.15 mmol of cerium nitrate are added to 50 mL of deionized water, and the amount of isopropanol used is 1 mL to 3 mL.

[0010] Furthermore, in S2, the microwave power is 400W~600W, and the microwave heating is carried out at 150℃~170℃ for 30min~50min.

[0011] Furthermore, in S3, the oxygen-containing atmosphere is air, the calcination temperature is 550℃~650℃, the heating rate is 8℃ / min~12℃ / min, and the calcination time is 2h~4h.

[0012] In another aspect, the present invention provides the application of the adsorbent prepared by the above-mentioned method based on the preparation of an asymmetric oxygen-vacancy iron-cerium composite oxide adsorbent, wherein the adsorbent is used to remove gaseous arsenic trioxide from high-temperature flue gas.

[0013] Furthermore, the high-temperature flue gas also contains at least one of water vapor, carbon dioxide, sulfur dioxide, or hydrogen chloride.

[0014] Furthermore, the temperature of the high-temperature flue gas is 200℃~900℃.

[0015] Furthermore, the adsorbent exhibits tolerance to carbon dioxide, sulfur dioxide, and hydrogen chloride in high-temperature flue gas.

[0016] Furthermore, after removing gaseous arsenic trioxide from the high-temperature flue gas, the adsorbent is regenerated by alkaline boiling with NaOH solution.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention relates to Fe constructed through cerium doping. 2+ -[O]-Ce 3+ The asymmetric oxygen vacancy greatly enhances the oxidizing capacity of the adsorbent. This oxygen vacancy can both activate free oxygen molecules (O2) in the flue gas and promote the migration of its own lattice oxygen. The two work together to efficiently oxidize highly toxic As2O3 into easily fixed As2O5, thus improving the arsenic adsorption capacity compared to unmodified H-Fe2O3.

[0018] 2. The adsorbent of this invention has significant structural advantages. A hollow microsphere structure composed of nanosheets was successfully constructed using the soft template method. This structure endows the material with excellent anti-sintering properties and thermal stability. Furthermore, the edges of the nanosheet structure and the amorphous phase expose a large number of active sites, which synergistically enhance the adsorption efficiency.

[0019] 3. The adsorbent of this invention exhibits excellent arsenic removal performance in a temperature range of 200℃ to 600℃, which is suitable for the wide temperature range of industrial flue gas.

[0020] 4. The adsorbent of the present invention can maintain a high adsorption efficiency of over 85% under complex flue gas composition (such as CO2, SO2, HCl), and especially exhibits a pattern of first promoting and then inhibiting water vapor.

[0021] 5. The asymmetric oxygen vacancies (Fe) in the adsorbent of this invention 2+ -[O]-Ce 3+ The key active center is the As2O3 oxidation site, which synergistically promotes the oxidation of As2O3 to As2O5 by activating molecular oxygen and providing active lattice oxygen, ultimately reacting with Fe. 3+ It is fixed by forming stable FeAsO4. Attached Figure Description

[0022] Figure 1 FeCeO prepared in Example 1 of this invention x-20% Microstructure diagram of the adsorbent; Figure 2 CeO2, Fe2O3, and FeCeO prepared in Example 1 x-20% Comparison of Raman spectra of adsorbents; Figure 3 This is a comparison of the EPR spectra of the two adsorbents prepared in Comparative Example 1 and Example 1 of this invention. Detailed Implementation

[0023] To facilitate understanding of the present invention, the present invention will be described more fully and in detail below with reference to preferred embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments.

[0024] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.

[0025] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.

[0026] The technical solutions of the present invention will now be clearly and completely described with reference to the accompanying drawings.

[0027] Example 1 This embodiment mainly investigates the optimal Ce doping amount and the effect of different doping amounts on arsenic adsorption capacity and adsorption efficiency. An asymmetric oxygen-vacancy iron-cerium composite oxide adsorbent and its preparation method are described below: S1. Preparation of precursor solution: First, take 0.8 mmol of urea, 0.5 mmol of ferric nitrate, 0.05 mmol of sodium citrate, and 0 mmol, 0.05 mmol, 0.10 mmol, and 0.15 mmol of cerium nitrate respectively (i.e., cerium-iron molar ratios of 0, 0.1, 0.2, and 0.3 respectively), add 50 mL of deionized water and 2 mL of isopropanol. Stir magnetically at 1000 rpm for 10 min to ensure complete dissolution and homogeneous mixing of all raw materials, thus obtaining the precursor solution.

[0028] S2. Three-dimensional structure construction: The precursor solution obtained in step S1 is transferred to a polytetrafluoroethylene container, heated to 160°C with a microwave power of 500W and kept at that temperature for 40 minutes. After cooling naturally to room temperature, the precipitate is separated by centrifugation, washed multiple times with ethanol, and then the resulting black precipitate is vacuum dried until the water is completely evaporated. S3. Calcination to remove the template: The dried black precipitate obtained in step S2 was placed in a muffle furnace and calcined at 10℃ / min to 600℃ under a 20% O2 + 80% N2 atmosphere for 3 hours to carbonize and remove the organic framework. After natural cooling, the resulting dark red precipitate was washed and filtered five times with anhydrous ethanol and deionized water, and then dried in a forced-air drying oven at 60℃ for 12 hours. Adsorbents H-Fe2O3 and FeCeO2 were obtained. x-10% FeCeO x-20% and FeCeO x-30% .

[0029] 50 mg of the above-mentioned adsorbent was taken and injected together with the simulated arsenic-containing flue gas into a quartz tube inside a muffle furnace. A filter cloth was installed at the end of the quartz tube to collect the adsorbent. The experimental conditions were as follows: the total arsenic trioxide content in the simulated flue gas was 0.5 mg, the flue gas flow rate was 0.1 L / min, the arsenic trioxide concentration in the flue gas was 0.0833 mg / L, the gas composition was 20% O2 + 80% N2, and the flue gas temperature was 600℃. The results are shown in Table 1.

[0030] Table 1

[0031] Table 1 compares the saturated adsorption capacity and capture efficiency of different adsorbents for arsenic under different Ce doping concentrations. The table shows that when the cerium content in the adsorbent is low (cerium-iron ratio 0.1:1), its arsenic capture efficiency is only 77.52%. However, when the iron-cerium ratio is precisely controlled at 0.2:1, the synergistic effect of the bimetallic compound is maximized, and the arsenic removal efficiency jumps directly to 93.88%. If the cerium content is further increased to 0.3:1, the efficiency decreases to 85.64%. This demonstrates that introducing a second metal (Ce) into a single iron-based framework to construct a composite oxide can significantly stimulate the oxidation adsorption potential of the material. It also confirms that precise elemental ratios are the core key to breaking through the performance ceiling of single-component materials.

[0032] FeCeO x-20% Microstructure of adsorbent such as Figure 1 As shown, the SEM image of the adsorbent surface ( Figure 1 a) EDS spectrum ( Figure 1 (b) TEM Figure 1 (c and d) and HR-TEM ( Figure 1 (e) Figure 1 It has been proven that FeCeO x-20% The adsorbent is a hollow microsphere structure with a diameter of 2 μm, and the surface of the adsorbent is composed of stacked iron oxide cerium composite amorphous nanosheets.

[0033] For CeO2, Fe2O3 and FeCeO x-20% Raman spectroscopy analysis was performed on the three materials, and the results are as follows: Figure 2 As shown, the CeO2 sample exhibits a velocity of 462 cm⁻¹. -1 The strong band centered on this element belongs to the F-type structure in cubic fluorite. 2g Symmetrical Raman mode. The Raman spectrum of Fe₂O₃ at 223 cm⁻¹. -1 289cm -1 414cm -1 and 614cm -1 Four peaks appear at this location, belonging to hematite (α-Fe₂O₃). For FeCeO₂...x-20% In the sample, the peak corresponding to α-Fe₂O₃ shifted to the left. This is because Ce doping causes impurities or defects to disrupt lattice symmetry, leading to Raman peak shift due to lattice reconstruction. Specifically, the 595 cm⁻¹ peak... -1 The peak value corresponds to the vacancy defect of cerium oxide itself, 485 cm⁻¹ -1 Corresponding to asymmetric vacancy defects, the existence of asymmetric vacancies was verified.

[0034] Example 2 In this embodiment 2, FeCeO was prepared using the method described in embodiment 1. x-20% As an adsorbent, its adsorption capacity for arsenic in high-temperature flue gas under different atmospheric conditions was studied.

[0035] The specific process for the arsenic adsorption capacity test is as follows: 50 mg of the prepared adsorbent was taken and the adsorbent and simulated arsenic-containing flue gas were injected into the quartz tube in the muffle furnace. The flue gas flow rate was 0.1 L / min, the arsenic trioxide content in the simulated flue gas was 0.2 mg, the arsenic trioxide concentration in the flue gas was 0.0333 mg / L, the reaction temperature was controlled at 600℃, and the flue gas composition was adjusted. The final arsenic removal efficiency in the flue gas is shown in Table 2.

[0036] Table 2

[0037] As shown in Table 2, under complex flue gas composition containing oxygen and sulfur dioxide, the adsorbent removal efficiency first increases and then decreases with increasing sulfur dioxide concentration, but the adsorption efficiency is still above 88.85%, indicating that the hollow microsphere structure adsorbent exhibits good tolerance and promoting effect on SO2 in flue gas. Similarly, the adsorbent also shows good tolerance to CO2, HCl, and H2O that may be present in flue gas, making it very suitable for capturing arsenic in smelting flue gas.

[0038] Example 3 Adsorption process: 20 mg of adsorbent H-Fe2O3 was injected together with the simulated arsenic-containing flue gas into a quartz tube inside a muffle furnace. A filter cloth was installed at the end of the quartz tube to collect the adsorbent. The experimental conditions were: arsenic content in the simulated flue gas was 1 mg, flue gas flow rate was 0.1 L / min, flue gas composition was 20% O2 + 80% N2, and adsorption temperature was 600℃.

[0039] Regeneration process: After adsorption saturation, desorption and thermal activation regeneration were performed using NaOH solution boiling method: the adsorbent after working was placed in NaOH solution (concentration 2 mol / L) and boiled at 100℃ for 2 h, so that the arsenate in FeAsO4 underwent ion exchange with OH- and was released, while regenerating the active sites of the adsorbent. The regenerated adsorbent was washed 3 times with deionized water and dried at 50℃ for 2 h before being used for the next adsorption cycle. The cycle test was performed 5 times, and the results are shown in Table 3.

[0040] Table 3

[0041] As shown in Table 3, after six alkaline boiling regenerations, the adsorption efficiency of the adsorbent remained above 82.7% of the initial value, indicating that the adsorbent has a stable structure, a simple and effective regeneration process, and has the potential for industrial application.

[0042] Comparative Example 1 This comparative study examines the effects of iron-cerium oxide adsorbents prepared by different synthesis methods on arsenic adsorption capacity and efficiency, including the FeCeO2 prepared in Example 1. x-20% FeCeO prepared by the following synthesis method x -1 Adsorbent.

[0043] FeCeO x The synthesis method of the adsorbent is shown below: (1) First, take 0.5 mmol of ferric nitrate and 0.10 mmol of cerium nitrate, add 50 mL of deionized water and 2 mL of isopropanol. Stir magnetically at 1000 rpm for 10 min to ensure that the added reagents are completely dissolved and mixed evenly.

[0044] (2) Transfer the solution obtained in step S1 to a polytetrafluoroethylene container, heat it to 160°C with a microwave power of 500W, keep it at that temperature for 40 minutes, cool it naturally to room temperature, separate the precipitate by centrifugation, wash it with ethanol several times, and then vacuum dry the obtained black precipitate until the water is completely evaporated.

[0045] (3) The dried black precipitate was placed in a muffle furnace and heated to 600°C at 10°C / min under an oxygen atmosphere. It was calcined for 3 hours to carbonize and remove the organic framework. After natural cooling, the resulting dark red precipitate was washed and filtered five times with anhydrous ethanol and deionized water, and then dried in a forced-air drying oven at 60°C for 12 hours to obtain FeCeO. x -1 Adsorbent.

[0046] Take 20 mg of FeCeO x-20% Adsorbent and FeCeO x -1 Adsorbent: The adsorbent and simulated arsenic-containing flue gas were injected into the quartz tube inside the muffle furnace. The flue gas flow rate was 0.1 L / min, the arsenic content in the simulated flue gas was 0.5 mg, the concentration of arsenic trioxide in the flue gas was 0.0833 mg / L, and the flue gas composition was 20% O2 + 80% N2. The comparison of arsenic adsorption capacity in a wide temperature range (200℃~900℃) is shown in Table 4 below.

[0047] Table 4

[0048] The results are shown in Table 4. Within this wide temperature range, the FeCeO of the present invention... x The saturated adsorption capacity of the adsorbent for As₂O₃ remained stable between 8.41 mg / g and 22.31 mg / g, reaching a peak of 22.31 mg / g at 500℃. Meanwhile, FeCeO₂… x The adsorption capacity of the powder in this temperature range is only 1.64 mg / g to 3.69 mg / g, which is significantly low, and the performance degradation is more obvious as the temperature increases.

[0049] EPR spectrometry was performed on the two adsorbents, and the results are as follows: Figure 2 As shown. Compared to FeCeO x -1,FeCeO x With a higher oxygen vacancy concentration, the unique synthesis method constructs a higher concentration of asymmetric oxygen vacancy sites. The adsorbent material synthesized by this invention through a unique soft template method not only endows the material with an extremely high initial specific surface area and abundant physical adsorption sites, but also fundamentally and effectively inhibits the sintering behavior of the material under high and ultra-high temperature environments, ensuring the integrity of the structure and achieving a leapfrog improvement in arsenic removal performance.

[0050] Comparative Example 2 This comparative study investigated the effect of different calcination atmospheres on the arsenic adsorption capacity and efficiency of the adsorbents during the template removal process in step S3. The specific steps were as follows: The pure nitrogen atmosphere in step S3 was replaced with pure O2 nitrogen, 10% O2 + 80% N2, 20% O2 + 80% N2, 30% O2 + 80% N2, and pure N2 nitrogen atmospheres, while maintaining all other conditions identical, resulting in different adsorbents. Adsorption tests were conducted at 600℃ using simulated arsenic-containing flue gas (containing 20% ​​O2 and equilibrium N2), following the same experimental method as in Example 1. The adsorption performance comparisons of the above adsorbents are shown in Table 5.

[0051] Table 5

[0052] The results are shown in Table 5. During the calcination of the adsorbent precursor, the number of oxygen vacancy sites generated by the adsorbent first increased and then decreased with the increase of oxygen concentration, and the arsenic removal performance also changed accordingly. Therefore, for better arsenic removal performance of the adsorbent, the calcination of the precursor in S3 is preferably carried out in an atmosphere of 20% O2 + 80% N2.

[0053] Comparative Example 3 This comparative study mainly examines the effects of different doping elements on arsenic adsorption capacity and adsorption efficiency.

[0054] This experimental example provides four adsorbents for removing arsenic from smelting flue gas. The synthesis method of the adsorbents is the same as in Example 1, except that the doping element is replaced by copper, aluminum, and nickel instead of cerium. The specific synthesis method is as follows: (1) First, take 0.8 mmol of urea, 0.5 mmol of ferric nitrate, and 0.05 mmol of sodium citrate, add them to 50 mL of deionized water and 2 mL of isopropanol. Then add 0.10 mmol of copper nitrate (Cu(NO3)2), cerium nitrate (Ce(NO3)4), aluminum nitrate (Al(NO3)3), and nickel nitrate (Ni(NO3)2) to the solution. Stir magnetically at 1000 rpm for 10 min to ensure complete dissolution and uniform mixing of the added reagents.

[0055] (2) Transfer the solution obtained in step S1 to a polytetrafluoroethylene container, heat it to 160°C with a microwave power of 500W, keep it at that temperature for 40 minutes, cool it naturally to room temperature, separate the precipitate by centrifugation, wash it with ethanol several times, and then vacuum dry the precipitate until the water is completely evaporated.

[0056] (3) The dried black precipitate was placed in a muffle furnace and calcined at 10℃ / min to 600℃ under a 20% O2 + 80% N2 atmosphere for 3 hours to carbonize and remove the organic framework. After natural cooling, the resulting precipitate was washed and filtered five times with anhydrous ethanol and deionized water, and then dried in a forced-air drying oven at 60℃ for 12 hours to obtain the adsorbent FeCeO. x FeCuO x FeNiO x FeAlO x .

[0057] Take 20 mg of adsorbent FeCeO x FeCuO x FeNiO x FeAlO x The adsorbent and simulated arsenic-containing flue gas were injected together into a quartz tube inside a muffle furnace. A filter cloth was installed at the end of the quartz tube to collect the adsorbent. The experimental conditions were: arsenic trioxide content in the simulated flue gas was 0.2 mg, flue gas flow rate was 0.1 L / min, arsenic trioxide concentration in the flue gas was 0.0333 mg / L, the gas composition was 20% O2 + 80% N2, and the flue gas temperature was 600℃. The arsenic removal performance of different adsorbents was investigated, and the results are shown in Table 6.

[0058] Table 6

[0059] Table 6 compares the saturated adsorption capacity and capture efficiency of four different doped metal adsorbents for arsenic. As can be seen from the table, FeCeO₂… x Compared to other metal adsorbents, Ce doping has an absolute advantage in adsorption capacity, making it the optimal solution.

[0060] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.

Claims

1. An adsorbent based on asymmetric oxygen-vacancy iron-cerium composite oxide, characterized in that, The adsorbent is a microsphere with a hollow mesoporous structure, the diameter of which is 1μm to 2μm and the shell thickness is 50nm to 100nm. The shell is formed by stacking iron oxide-cerium composite amorphous nanosheets with an average particle size of 5nm to 10nm, and Fe is constructed by cerium doping. 2+ -[O]-Ce 3+ Asymmetric oxygen vacancies.

2. The preparation method of the asymmetric oxygen-vacancy iron-cerium composite oxide adsorbent according to claim 1, characterized in that, The preparation method includes the following steps: S1. Preparation of precursor solution: Add urea, sodium citrate, ferric nitrate and cerium nitrate in a preset ratio to deionized water, stir evenly, then add isopropanol and mix evenly to form a precursor solution. S2. Three-dimensional structure construction: The precursor solution is microwave heated to the target temperature and kept at that temperature, then naturally cooled to room temperature. The precipitate is collected by centrifugation, washed with ethanol, and then vacuum dried until the water is completely evaporated to obtain a black precipitate. S3. Calcination to remove template: The black precipitate is placed in a muffle furnace and calcined in an oxygen atmosphere. After natural cooling, it is washed and filtered with anhydrous ethanol and deionized water, and dried to obtain a dark red powder.

3. The preparation method of an asymmetric oxygen-vacancy iron-cerium composite oxide adsorbent according to claim 2, characterized in that, In S1, 0.7 mmol to 0.9 mmol of urea, 0.04 mmol to 0.06 mmol of sodium citrate, 0.4 mmol to 0.6 mmol of nitric acid, and 0.05 mmol to 0.15 mmol of cerium nitrate are added to 50 mL of deionized water, and the amount of isopropanol used is 1 mL to 3 mL.

4. The preparation method of an asymmetric oxygen-vacancy iron-cerium composite oxide adsorbent according to claim 2, characterized in that, In S2, the microwave power is 400W~600W, and the microwave heating is carried out at 150℃~170℃ for 30min~50min.

5. The preparation method of an asymmetric oxygen-vacancy iron-cerium composite oxide adsorbent according to claim 2, characterized in that, In S3, the oxygen atmosphere is air, the calcination temperature is 550℃~650℃, the heating rate is 8℃ / min~12℃ / min, and the calcination time is 2h~4h.

6. The application of the adsorbent based on the asymmetric oxygen-vacancy iron-cerium composite oxide adsorbent according to claim 1 or the adsorbent prepared by the preparation method of the asymmetric oxygen-vacancy iron-cerium composite oxide adsorbent according to any one of claims 2 to 5, characterized in that, The adsorbent is used to remove gaseous arsenic trioxide from high-temperature flue gas.

7. The application according to claim 6, characterized in that, The high-temperature flue gas also contains at least one of water vapor, carbon dioxide, sulfur dioxide, or hydrogen chloride.

8. The application according to claim 6 or 7, characterized in that, The temperature of the high-temperature flue gas is 200℃~900℃.

9. The application according to claim 7, characterized in that, The adsorbent exhibits tolerance to carbon dioxide, sulfur dioxide, and hydrogen chloride in high-temperature flue gas.

10. The application according to claim 6, characterized in that, After removing gaseous arsenic trioxide from the high-temperature flue gas, the adsorbent is regenerated by alkaline boiling with NaOH solution.